2002
DOI: 10.1161/hy0202.103288
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase Inhibition Attenuates Renal Hemodynamics During Pregnancy

Abstract: Abstract-Acute, nonselective nitric oxide synthase inhibition in the pregnant rat decreases glomerular filtration rate and renal plasma flow, suggesting a role for nitric oxide in mediating renal vasodilation during pregnancy. As mid-gestation in the rat is associated with a significant increase in renal protein expression of inducible nitric oxide synthase, the aim of this study was to examine the role of inducible nitric oxide synthase in mediating renal hemodynamics changes at mid-gestation in the rat. At d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…These hypotheses are supported by previous results implicating iNOS in experimental hypertension [14]. In contrast with our hypothesis, there is evidence that iNOS has an important role in the renal hemodynamic changes of pregnancy, and iNOS inhibition decreased glomerular filtration in pregnant rats [15], although renal iNOS apparently is not up-regulated in RUPP rats [12]. …”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…These hypotheses are supported by previous results implicating iNOS in experimental hypertension [14]. In contrast with our hypothesis, there is evidence that iNOS has an important role in the renal hemodynamic changes of pregnancy, and iNOS inhibition decreased glomerular filtration in pregnant rats [15], although renal iNOS apparently is not up-regulated in RUPP rats [12]. …”
Section: Introductionsupporting
confidence: 86%
“…Although we have not measured iNOS activity in this study, the 1400 W that we used (1 mg/kg) totally prevented vascular injury attributable to LPS-induced iNOS in rats (ED 50 = 0.3 mg/kg) [16]. Interestingly, other iNOS inhibitors were shown to increase blood pressure in normal rats [15], possibly as a result of non-selective iNOS inhibition, whereas our findings showed antihypertensive effects with 1400 W, possibly as a result of selective iNOS inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of isoform-"selective" NOS inhibitors has implicated neuronal and inducible NOS (nNOS and iNOS) (1,3), while lack of endothelial NOS (eNOS)-selective inhibitors has prevented direct investigation of eNOS. Alexander et al (4) reported an increase in nNOS protein abundance in rats at midterm, which coincides with maximal renal vasodilation (5), while an unexpected decline in eNOS protein abundance was also observed.…”
mentioning
confidence: 99%
“…NO, the product of NO synthases (NOSs), possesses anti-inflammatory and vasodilative activity and is anti-apoptotic through Akt signaling pathways (13)(14)(15)(16)(17). Sex hormones are known to regulate NO synthesis (18,19).…”
mentioning
confidence: 99%